The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1590/1679-775720130204
|View full text |Cite
|
Sign up to set email alerts
|

Abrasion of 6 dentifrices measured by vertical scanning interference microscopy

Abstract: ObjectivesThe abrasion of dentifrices is well recognized to eliminate the dental plaque. The aims of this study were to characterize the abrasive powders of 6 dentifrices (3 toothpastes and 3 toothpowders) and to measure the abrasion on a test surface by Vertical Scanning Interference microscopy (VSI). Material and MethodsBright field and polarization microscopy were used to identify the abrasive particles on the crude dentifrices and after prolonged washes. Scanning electron microscopy and microanalysis chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Particle size and shape are also found to influence abrasion, particularly when comparing abrasives made from the same compound, as silicon dioxide (artificial silica) (15). This study presented some dentifrices with irregular and large particles, demonstrating greater abrasiveness.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Particle size and shape are also found to influence abrasion, particularly when comparing abrasives made from the same compound, as silicon dioxide (artificial silica) (15). This study presented some dentifrices with irregular and large particles, demonstrating greater abrasiveness.…”
Section: Discussionmentioning
confidence: 81%
“…The desiccation loss in the present study was similar among the groups. Sensodyne Original (64.07%), Sensodyne Cool Gel (60.85%) and Sensodyne Branqueador (65.83%) showed greater content of abrasive agents, but other studies found no correlation between the content of abrasives and abrasion degree (15,16).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…This is corroborated by data from this study where effective biofilm removal without a detrimental effect to the substratum was observed at short exposure times (10 s). Longer exposure times of 10 min did cause an increase in surface roughness on a hydroxyapatite surface; however, this should be put into context of other studies where exposure of 2 min to toothbrushing using certain dentrifices produced a much greater surface abrasion than observed with a 10-min UAS exposure (Pascaretti-Grizon et al 2013). In addition, while the flow rate of 2.1 L/min used in this study provides good surface area coverage, there is the issue of requiring relatively large volumes of water, and thus miniaturization would be desirable.…”
Section: Discussionmentioning
confidence: 76%
“…The relation between the abrasive potential of toothpastes, alterations on enamel and restorative materials has been evaluated by many studies [35]. In fact, it was reported by Pinto et al [7] that dentifrices abrasiveness might be affected by the quality and the quantity of abrasives, unlike other studies, where no correlation between the content of abrasives and abrasion degree has been detected [36]. In the present study, sodium carbonate and calcium carbonate were used as combined abrasive agents for formula 2, similarly to Moore and Addy [37] who formulated toothpaste with a combination of different abrasive agents (artificial silicas, tixosil, Zeodent and calcium carbonate).…”
Section: Discussionmentioning
confidence: 99%